Grewia asiatica L., a Food Plant with Multiple Uses - Vincenzo De Feo; Komal Rizwan; Milan S. Stanković; Muhammad Zia-Ul-Haq (Molecules, 2013)
Grewia asiatica L., is a species native to south Asia from Pakistan, east to Cambodia, cultivated primarily for its edible fruit and well-reputed for its diverse medicinal uses. Fruits are a rich source of nutrients such as proteins, amino acids, vitamins, and minerals and contain various bioactive compounds, like anthocyanins, tannins, phenolics and flavonoids. Different parts of this plant possess different pharmacological properties. Leaves have antimicrobial, anticancer, antiplatelet and antiemetic activities; fruit possess anticancer, antioxidant, radioprotective and antihyperglycemic properties; while stem bark possesses analgesic and anti-inflammatory activities. This review focuses on the botanical description, phytochemistry, nutritional studies and pharmacological properties of this plant.